2020
DOI: 10.1002/er.6076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of silver nanoparticles (AgNPs) derived from actinomycetes and henna on biohydrogen production by Clostridium beijerinckii (KTCC1737)

Abstract: The current study comparatively evaluated the effects of silver nanoparticles (AgNPs) on fermentative bio hydrogen (bio-H 2 ) production by Clostridium beijerinckii (KTCC1737). Green synthesized AgNPs were fabricated using henna (Lawsonia inermis) and DU-C2 actinomycete in batch using different AgNPs concentrations (0, 40, 80, and 120 μg/mL). The overall results revealed that after 72 hours of AgNPs incubation with C beijerinckii, the henna mediated AgNP synthesis increased the hydrogen production rate with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The results implied that the B20 blend, which reduced the amount of 20% pure diesel fuel, could be utilized in place of plain diesel if preferred. Khan et al (2021) employed henna and actinomycete DU-C2 in the production of AgNPs for biohydrogen production. In batch configurations, Clostridium beijerinckii was incubated with henna-mediated AgNPs at concentrations of 0, 40, 80, and 120 g/ml for 72 h, resulting in an increase in hydrogen production with a yield of 1.71 mol H2/mol added glucose.…”
Section: Biofuel and Biohydrogen Productionmentioning
confidence: 99%
“…The results implied that the B20 blend, which reduced the amount of 20% pure diesel fuel, could be utilized in place of plain diesel if preferred. Khan et al (2021) employed henna and actinomycete DU-C2 in the production of AgNPs for biohydrogen production. In batch configurations, Clostridium beijerinckii was incubated with henna-mediated AgNPs at concentrations of 0, 40, 80, and 120 g/ml for 72 h, resulting in an increase in hydrogen production with a yield of 1.71 mol H2/mol added glucose.…”
Section: Biofuel and Biohydrogen Productionmentioning
confidence: 99%
“…Green silver nanoparticles are examined as the best catalyst for biohydrogen production. Khan et al 86 performed biohydrogen production with the supplementation of silver nanoparticles by C beijerinckii . The green silver nanoparticles were synthesized with henna plant ( Lawsonia inermis ) and actinomycete.…”
Section: Types Of Metal Nanoparticles In Biohydrogen Productionmentioning
confidence: 99%
“…The fermentation was confirmed to be changed to ethanol-type from butyrate-type through respective bacterial abundance. Khan et al 154 demonstrated that green synthesized Ag nanoparticles through two ways namely henna with C beijerinckii KTCC and actinomycetes showed varied effects on biohydrogen production. The latter inhibited whereas former increased the hydrogen yield after 72 h incubation period.…”
Section: Biohydrogen Productionmentioning
confidence: 99%